Literature Analysis on the Use of Computer Based Test (CBT) in Ensuring the Quality of New Student Input in Higher Education Selection - Bodhi Ratana Ratana (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2026)
Digital transformation in higher education requires an evaluation system that ensures administrative efficiency as well as high accuracy in capturing the quality of student input. This study aims to synthesize the urgency of using Computer Based Test (CBT) as a high-stakes selection instrument that focuses on the efficiency, validity of the instrument, and system security. Using a qualitative-descriptive literature study method, data was analyzed from reputable scientific sources published from 2020 to 2025. The findings show that CBT significantly optimizes managerial efficiency through automated assessment and real-time data processing. In addition, the integration of Computerized Adaptive Testing (CAT) and automated question item analysis improves the validity of the content, allowing for more objective measurement of cognitive ability. However, the integrity of the selection results relies heavily on strong security protocols, such as the Safe Exam Browser (SEB), to mitigate digital fraud. In conclusion, the use of CBT is a crucial strategy to reconstruct a more intelligent, fair, and adaptive selection model. Ensuring the quality of new student input is optimally achieved if the sophistication of the software is supported by a valid question bank and a strong cybersecurity infrastructure to maintain academic credibility in the digital era.